Предмет: Алгебра,
автор: Синдик
Упростите выражения
(а^2+aх/х)/а+х/х^2)
Ответы
Автор ответа:
0
если я правильно поняла, то:
((а² + ах)/х)/((а + х)/х²) = ((а² + ах)*х²)/(х(а + х)) = (а(а + х) * х²)/(х(а+х) = ах
Автор ответа:
0
(а^2+aх/х)/а+х/х^2)=(а^2+a)/а+1/х)=(а (а+1))/а+1/х)= (а+1)+1/х=((а+1)+1)/х=(ах+х+1)/х
Похожие вопросы
Предмет: Русский язык,
автор: Аноним
Предмет: Геометрия,
автор: Аноним
Предмет: История,
автор: amira5811
Предмет: Математика,
автор: Reset232
Предмет: Алгебра,
автор: Feorina